2020
DOI: 10.1021/acsphotonics.9b01625
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Beam Generation by Spin-Orbit Interaction with Bloch Surface Waves

Abstract: Axis-symmetric grooves milled in metallic slabs have been demonstrated to promote the transfer of Orbital Angular Momentum (OAM) from far- to near-field and vice versa, thanks to spin-orbit coupling effects involving Surface Plasmons (SP). However, the high absorption losses and the polarization constraints, which are intrinsic in plasmonic structures, limit their effectiveness for applications in the visible spectrum, particularly if emitters located in close proximity to the metallic surface are concerned. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[ 58 ] Recently, Stella et al demonstrated an alternative mechanism for far‐field OV generation based on the diffraction of Bloch surface waves, as depicted in Figure 5d. [ 66 ] A spiral grating on top of the dielectric multilayers induced designated phase distributions and diffracted the Bloch surface waves into the far‐field.…”
Section: Characterization Of Psois In the Near‐field Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 58 ] Recently, Stella et al demonstrated an alternative mechanism for far‐field OV generation based on the diffraction of Bloch surface waves, as depicted in Figure 5d. [ 66 ] A spiral grating on top of the dielectric multilayers induced designated phase distributions and diffracted the Bloch surface waves into the far‐field.…”
Section: Characterization Of Psois In the Near‐field Wavesmentioning
confidence: 99%
“…Reproduced with permission. [ 66 ] Copyright 2020, American Chemical Society. e) Tunable unidirectional coupling by coupling SAM into curved nanoscale plasmonic waveguides, where a circular decoupler is fabricated at the end of each route to visualize the optical flow.…”
Section: Characterization Of Psois In the Near‐field Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Through careful design of each element structure, the metal metasurfaces can provide an additional phase gradient or surface momentum [22,23]. Metal metasurfaces based on the Pancharatnam-Berry (PB) phase [24] or geometric phase can produce OVs through the spin-orbit interaction (SOI) [25], which are robust and nondispersive [26]. Although these surfaces have multiple functions, they still face some obvious challenges and shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to surface plasmon polaritons, it was examined whether or not electromagnetic modes can be sustained bound at the interface between air and a finite dielectric photonic crystal. The possible appearance of air/photonic crystal localized states have attracted great attention due to the fact that, with the addition of a supplementary defect, they may couple to external radiation in a controlled way, being transformed into a leaky mode. This enables fascinating applications like beam wavefront steering and beam shaping, further facilitating the communication of the components in a photonic crystal circuit. It was found that, in the typical two-dimensional rectangular dielectric photonic crystal, we need a corrugation, that is, a layer of different size, material, or lattice, to sustain the bound mode .…”
mentioning
confidence: 99%